The ox that gored [large type] - Crownover, James D. (Wheeler large print western series., 2018)
"Lee Sowell, a would-be bootlegger and outlaw, is compelled by Judge Isaac Parker to become a U.S. deputy marshal. He receives his training under the tutelage of famed deputy Bass Reeves and becomes a deputy with a posse of his own, ranging across the Indian Territory chasing bootleggers, murderers, and robbers. Creek Indian Lighthorse police bring Lee a man accused of murdering a young girl he had kidnapped. This is Lee's first encounter with A.B. Chew, a pathological murderer. Other adventures include an encounter with New Mexican comancheros and a gang of stock thieves operating along the cattle trails. Lee is captured by Seminole warriors and is suspected of being the thief who stole their horses. Chief Puma shows Lee how the Seminole take care of horse thieves. Lee and his posse rescue Deputy U.S. Marshal Tracey Price and his posse, who have been captured by cattle thieves, and are being taken to the Comanche Indians for torture. Later, Price and his posse disappear in the western Indian Territory and Judge Parker sends Lee to find them. What they find sends them on a manhunt across the territory that ends in a showdown at Robbers' Roost in the Cimarrón Strip"--